Construction and validation of educational materials for the prevention of metabolic syndrome in adolescents - Ionara Holanda de Moura; Antônia Fabiana Rodrigues da Silva; Aparecida do Espírito Santo de Holanda Rocha; Luisa Helena de Oliveira Lima; Thereza Maria Magalhães Moreira; Ana Roberta Vilarouca da Silva (Universidade de São Paulo, 2017)
ABSTRACT Objective: To develop and validate an educational technology focused on prevention of metabolic syndrome among adolescents. Methods: This was methodological research. Using an integrative review, the available publications on the subject were analyzed. Then, this knowledge was used to describe the theoretical content and, with the help of a graphic designer, the art and layout of the pages were developed. In the third phase, the booklet was evaluated and validated by 21 specialists and 39 adolescents. Data collection included three different questionnaires, according to the focus of evaluation of each group of participants, analyzed for reliability (Cronbach's Alpha) and agreement by Infraclass Correlation Coefficient. Results: The mean score attributed by technical content experts was 91.7%, and the content validity index, measured by experts responses, was 0.98, showing high reliability and agreement. In addition, the level of agreement of the positive responses given by adolescents was 88.4%. Conclusion: the educational booklet has proved to be a valid and reliable tool to be used for promoting adolescent health.